Mental illness in some Sub Saharan African communities: the perspective of Bioethics and transcultural nursing - Maccaro, Alessia; Piaggio, Davide; Dodaro, Concetta Anna; Pecchia, Leandro (Medicina e Morale, 2020)
In this paper, transcultural nursing is reviewed in light of bioethical issues arising from the interpretation of mental illness in some Western Sub-Saharan African communities. Four field studies were carried out by the authors of this paper in Sub-Saharan Africa (from 2016 to 2019), during which the traditional "treatment" of enchaining people considered "crazy" by local cultures was explored. These inhuman practices raise the attention of bioethics, which investigate ways to overcome this traditional practice not violating the cultural identity of the peoples who practice it. The model of Gregoire Ahongbonon and of his Association, "Saint Camille de Lellis", is reported as an example of negotiation between the respect for traditions and the guarantee of human rights. The care practice in force in the Saint Camille is related to transcultural nursing as an adequate form of treatment and strategy for restoring patients' dignity and rights.